The cytosolic N-terminal domain of V-ATPase a-subunits is a regulatory hub targeted by multiple signals - Tuli, Farzana; Kane, Patricia M. (Frontiers in Molecular Biosciences, 2023)
Vacuolar H+-ATPases (V-ATPases) acidify several organelles in all eukaryotic cells and export protons across the plasma membrane in a subset of cell types. V-ATPases are multisubunit enzymes consisting of a peripheral subcomplex, V1, that is exposed to the cytosol and an integral membrane subcomplex, Vo, that contains the proton pore. The Vo a-subunit is the largest membrane subunit and consists of two domains. The N-terminal domain of the a-subunit (aNT) interacts with several V1 and Vo subunits and serves to bridge the V1 and Vo subcomplexes, while the C-terminal domain contains eight transmembrane helices, two of which are directly involved in proton transport. The a-subunit is encoded by the largest number of isoforms in most organisms. For example, the human genome encodes four a-subunit isoforms that exhibit a tissue- and organelle-specific distribution. In the yeast S. cerevisiae, the two a-subunit isoforms, Golgi-enriched Stv1 and vacuolar Vph1, are the only V-ATPase subunit isoforms. Current structural information indicates that a-subunit isoforms adopt a similar backbone structure but sequence variations allow for specific interactions during trafficking and in response to cellular signals. V-ATPases are subject to several types of environmental regulation that serve to tune their activity to their cellular location and environmental demands. The position of the aNT domain in the complex makes it an ideal target for modulating V1-Vo interactions and regulating enzyme activity. The yeast a-subunit isoforms are a paradigm for dissecting interactions of regulatory inputs with subunit isoforms. Importantly, structures of yeast V-ATPases containing each a-subunit isoform are available. Chimeric a-subunits combining elements of Stv1NT and Vph1NT have provided insights into how regulatory inputs can be integrated to allow V-ATPases to support cell growth under different stress conditions. Although the function and distribution of the four mammalian a-subunit isoforms present additional complexity, it is clear that the aNT domains of these isoforms are also subject to multiple regulatory interactions. Regulatory mechanisms that target mammalian a-subunit isoforms, and specifically the aNT domains, will be described. Altered V-ATPase function is associated with multiple diseases in humans. The possibility of regulating V-ATPase subpopulations via their isoform-specific regulatory interactions are discussed.